Electrochemical behaviour of titanium-bearing slag relevant for molten oxide electrolysis. (10th September 2020) - Martin-Treceno, Samuel; Weaver, Nicholas; Allanore, Antoine; Bishop, Catherine M.; Marshall, Aaron T.; Watson, Matthew J.
Abstract: A containerless approach was used to investigate the electrochemical behaviour of TiO 2 − SiO 2 − Al 2 O 3 − MgO − CaO slags in their molten state. Iridium was used in a three-electrode configuration to perform a combination of electrochemical techniques inside a modified thermal imaging furnace. The real-time visualization during experimentation and the post-mortem microscopy analysis confirmed the direct production of an Ir − Ti − Si alloy and the evolution of oxygen during electrolysis. Thermodynamic properties of the slag were predicted with FactSage and were consistent with experiment. The results justify the use of this method to better characterize the potential of these systems as a secondary source of materials. Highlights: Molten slag electrolysis was performed in a modified thermal imaging furnace. A metallic Ir – Ti – Si product region was identified after electrolysis. The reduction of metals was consistent with thermodynamic predictions. A methodology is presented to accelerate the characterization of Ti-bearing slags.